2018
DOI: 10.1007/s10899-018-9806-7
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Behaviors and Problem Gambling: A Population-Based Comparison of Transgender/Gender Diverse and Cisgender Adolescents

Abstract: Most gambling research utilizes general youth samples and focuses on binary gender categories; few studies examine and compare gambling behaviors between transgender and gender diverse (TGD) youth and their cisgender peers. The current study used population-based data from the 2016 Minnesota Student Survey to compare the prevalence of gambling behaviors and problem gambling among TGD versus cisgender adolescents, in addition to examining differences by birthassigned sex. The analytic sample consisted of 80,929… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Another study assessed gambling behaviour among transgender diverse and cisgender populations. Both male and female assigned at birth transgender adolescents had higher problem gambling than cisgender males and females [37].…”
Section: Vulnerable Populationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Another study assessed gambling behaviour among transgender diverse and cisgender populations. Both male and female assigned at birth transgender adolescents had higher problem gambling than cisgender males and females [37].…”
Section: Vulnerable Populationsmentioning
confidence: 90%
“…Most studies observed whether young people had ever participated in gambling or had gambled within the previous 12 months, and reported the prevalence of problem gambling, which was typically reported as low or moderate risk of problem gambling, or problem gambling. Lifetime participation in gambling rates ranged between 42.1% [10] and 89.9% [20], with the majority of studies that examined gambling participation reporting that around a third or more of adolescents or young adults confirmed that they had gambled at least once in their lifetime [10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Gambling participation rates during the past 12 months ranged between 18.6% [38] to 85% [23].…”
Section: Gambling Participation and Problem Gamblingmentioning
confidence: 99%
“…Only 1.7% of the articles on the socio-cultural analysis of gender or 0.04% of the total articles in this scoping review have looked beyond the socio-cultural construction of gender binary and focused on the complexity and fluidity of gender. Among the 2,532 analyzed articles, only the article by Rider et al (2019) titled "Gambling Behaviors and Problem Gambling: A Population-based Comparison of Transgender/Gender Diverse and Cisgender Adolescents" stressed the fundamental requirement for gambling studies to move beyond the man/woman binary to acknowledge the fluidity of gender constructions in their discussion of the gambling behaviours of gender-diverse adolescents. Rider et al (2019) highlighted how gambling studies tend to aggregate gender-diverse groups without distinguishing between them.…”
Section: Essentializing the Binary Representation Of Sex And Gendermentioning
confidence: 99%
“…However, rather than problematizing gender and addressing gender fluidity in their sample of genderdiverse adolescents, Rider et al (2019) focused on how gambling risk manifested within a male/female binary structure of biological sex rather than gender. Consequently, we concur that gambling scholarship needs to extend beyond simple comparisons and binary representations to perceive gambling as a gendered activity that exposes how gender in gambling is constructed and negotiated (Järvinen-Tassopoulos, 2016a).…”
Section: Essentializing the Binary Representation Of Sex And Gendermentioning
confidence: 99%
“…There is a limited but revealing body of research investigating behavioral addictions as a function of gender identity. For instance, a 2019 study of 2168 transgender young adults determined that the prevalence of past year gambling was similar between transgender and cisgender populations (29.6% vs. 31.7%) [54]. However, when participants were assessed for pathological gambling (PG), it was determined that, while still very low, the prevalence of PG was nearly three times higher among TGD people compared to cisgender individuals (1.43% vs. 0.49%).…”
Section: Behavioral Addictionsmentioning
confidence: 99%